2021
DOI: 10.18203/2394-6040.ijcmph20213689
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between internet gaming disorder and insomnia among medical college students of Kanchipuram district, Tamil Nadu

Abstract: Background: Excessive online gaming poses a big problem among the growing generation. It leads to poor quality of sleep among students.Methods: It is a cross-sectional study done among medical college students of a tertiary care hospital, Kanchipuram district, Tamil Nadu for a period of 6 months (May to October 2019). 376 students participated in this study. Data was collected using self-administered questionnaire containing IGDS9-SF and ISI scales. Data was analysed using SPSS version 21.Results: Of the 376 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The prevalence of gaming addiction in present study was 32%, much higher than studies done at Kanchipuram (4.25%) [15] and Ludhiana(9%). [16] Both the studies used IGDS9-SF scale for assessment which is used in the present study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The prevalence of gaming addiction in present study was 32%, much higher than studies done at Kanchipuram (4.25%) [15] and Ludhiana(9%). [16] Both the studies used IGDS9-SF scale for assessment which is used in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…The present study showed a statistically significant association between insomnia and gaming addiction (p<0.0001), similar to a study done at Kanchipuram, Tamil Nadu. [15] Possible reason may be the availability of a variety of games online.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Contrary to the present study, a number of studies found that sleep disturbance was associated with IGD. 14 , 17 , 25 , 26 This contradiction concerning the association between sleep behavior and IGD could be possibly due to different measurement tools used in other studies or may be because the study participants were really able to manage their regular sleep regardless of IGD. Physical pain was significantly associated with IGD in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Similar studies were conducted in India, and the prevalence of IGD was 3.5% among adolescent school children in Andhra Pradesh, 4 3.6% in New Delhi, 9 and 4.25% in Kanchipuram district of Tamil Nadu. 14 In other nations, a prevalence rate of 21.8% was reported among male high school students in the Eastern region of Dammam, Saudi Arabia, 15 10.3% among Chinese students, 16 9.2% among Lebanese students, 17 5.9% among Korean students, 18 2.03% among Indonesian medical students, 19 5.4% among secondary school students in Thailand, 20 and 5.06% among advanced students in Sri Lanka. 21 The variations may be due to the different scales used to assess the prevalence of IGD, sociocultural distinctions, differences in targeted demographics, and differences in sample sizes in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation